Peningkatan Kompaktibilitas Metformin HCl Melalui Kokristalisasi Menggunakan Koformer Asam Suksinat - Izzazahra Tijani Fathya Ayyaru (Fakultas Farmasi, 2024)
Metformin hydrochloride is a biguanid hypoglycemic drug for first-line therapy of type II diabetes mellitus. Metformin hydrochloride has a tensile strength value of not more than 0.5 Mpa which indicates that the resulting compactibility is poor. One method that is often used to improve the compactibility properties of BAF is through the formation of cocrystallization. Pharmaceutical cocrystals contain two or more compounds in a stoichiometric ratio through noncovalent interactions. Characterization analysis was carried out using PXRD, FTIR, DSC, and SEM tests to determine the different characters in the cocrystal samples and their constituent components. One of the parameters for evaluating the compactibility of metformin HCl and metformin HCl-succinic acid cocrystals was carried out using the calculation of the tensile strength value and the percentage of elastic recovery (%ER). Preparation of metformin-succinic acid cocrystals by solvent evaporation method using molar ratio of metformin as active ingredient and succinic acid as coformer which is 1:1. Analysis of compactibility data was carried out using software with the SPSS Statistic 26.0 for windows test. Statistical analysis was carried out with the Independent T-Test test if the resulting data normality was met, while the alternative to the Independent T-Test test if the resulting data normality was not met was carried out with the Mann-Whitney test. Characterization results (PXRD, DSC, FTIR, and SEM) of metformin HCl succinic acid cocrystals showed the formation of metformin HCl-succinic acid cocrystals. Metformin HCl-succinic acid cocrystals showed better tensile strength and elastic recovery percentage compared to pure metformin HCl. So it can be concluded that metformin HCl cocrystal with succinic acid can improve the compactibility of pure metformin HCl.
Reupload File Repository 9 Juni 2026_Yudi
Keywords: Cocrystal; Metformin Hydrochloride; Succinic Acid; Solvent evaporation; Compatibility Properties